Three-Dimensional Surface Deviation Maps for Analysis of Retrieved Polyethylene Acetabular Liners Using Micro-Computed Tomography - Teeter, Matthew G.; Naudie, Douglas D.R.; Charron, Kory D.; Holdsworth, David W. (The Journal of arthroplasty, 2010)
Micro-computed tomography (micro-CT) has previously been validated for measuring wear volume in polyethylene acetabular liners. The creation of 3-dimensional (3D) articular and backside surface deviation maps using micro-CT is described. An acetabular liner was retrieved after 16.7 years of implantation and scanned with micro-CT along with a new, never-implanted liner of the same size and type. The liner surface geometries were reconstructed and co-aligned. A 3D comparison and cross-sectional analysis was performed. Maximum 3D deviation of the articular surface was −2.48 ± 0.02 mm, with maximum backside deviation of 0.46 ± 0.02 mm. Micro-CT can measure surface deviation and therefore calculate the volume of wear plus creep of retrieved acetabular liners, and may be applicable for wear simulator studies and analyzing other polyethylene components including tibial inserts.